2014
DOI: 10.1007/s11999-014-3593-y
|View full text |Cite
|
Sign up to set email alerts
|

Increased Rates of Periprosthetic Joint Infection in Patients With Cirrhosis Undergoing Total Joint Arthroplasty

Abstract: Background Total joint arthroplasty (TJA) is becoming more prevalent, with additional increases in procedure rates expected as the US population ages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
3
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 26 publications
1
40
3
1
Order By: Relevance
“…Our study found that patients with cirrhosis in both the THA and TKA groups had increased odds of developing acute postoperative anemia, thrombocytopenia, hematoma/hemorrhage, acute renal failure, device-related complications, infection, and complications of medical care. In a study that utilized a statewide database, Jiang et al[12] studied the periprosthetic joint infection rate in patients with cirrhosis and found that infections were significantly more common in patients with cirrhosis compared to those controls after THA (3.7% vs. 0.7%, p<0.001) and TKA (2.7% vs. 0.8%, p<0.001). The cirrhosis patients also had significantly increased LOS, readmission, reoperation, mortality and costs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study found that patients with cirrhosis in both the THA and TKA groups had increased odds of developing acute postoperative anemia, thrombocytopenia, hematoma/hemorrhage, acute renal failure, device-related complications, infection, and complications of medical care. In a study that utilized a statewide database, Jiang et al[12] studied the periprosthetic joint infection rate in patients with cirrhosis and found that infections were significantly more common in patients with cirrhosis compared to those controls after THA (3.7% vs. 0.7%, p<0.001) and TKA (2.7% vs. 0.8%, p<0.001). The cirrhosis patients also had significantly increased LOS, readmission, reoperation, mortality and costs.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, patients with cirrhosis who undergo elective surgery have compensated cirrhosis[11]. Over the past decade, as the medical care for cirrhosis has improved and the number of patients living with cirrhosis increases[2], there has been an increase in the number of cirrhotic patients undergoing primary total joint arthroplasty (TJA)[12]. Complications due to cirrhosis following total hip arthroplasty (THA) and total knee arthroplasty (TKA) can lead to an increased risk of perioperative morbidity and mortality[8,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While worse outcomes have been documented among patients with liver cirrhosis undergoing primary total hip (THA) and knee (TKA) arthroplasty [14,15], the influence of alcohol misuse, without cirrhosis, on perioperative outcomes following total joint arthroplasty is poorly understood. One study by Williams-Russo et al [16] evaluated 60 patients undergoing bilateral TKA and found that pre-operative alcohol use was associated with an increased risk of delirium in geriatric patients.…”
mentioning
confidence: 99%
“…Also, patients with liver cirrhosis readmitted because of PJI had an increased rate of mortality (0.7% compared with 4.4%; P ¼ 0.003). 40 …”
Section: Identification Of Risk Factors For Pjimentioning
confidence: 99%